FKASA holds 3rd National Conference on Wind & Earthquake Engineering - Emma Melati, Burhanuddin (2019)
The Faculty of Civil Engineering & Earth Resources (FKASA), Universiti Malaysia Pahang (UMP) continues its legacy of being the pioneer in the East Coast of Malaysia by organizing the third annual National Conference on Wind & Earthquake Engineering (NCWE) at Impiana KLCC Hotel in Kuala Lumpur on July 12, 2019.